Future homes with the application of ancient building experience, new structural techniques, and natural energy consumption - Tian, Changqing; Shahraki, Abdol Aziz (Journal of Environmental Engineering and Landscape Management, 2023)
This study analyses some characteristics of ancient construction and clarifies how they used renewable energy in their homes. This article analyzes ancient houses that were nature-oriented and used renewable energy. This study focuses on the structural system of ancient houses in Sistan. It dissects the structural elements of the old homes. The autopsy of the ancient house structure of Sistan shows the reader the techniques used in ancient architecture to provide energy. The research methods of this article are to examine the energy supply experiences of houses in the form of a case study of an old Sistan house to discover their energy-supplying techniques. This article uses the techniques used in Sistani houses with the application of modern house-building technologies, to develop a nature-oriented model. In fact, the model presented in this article is a modernized version of the ancient house of Sistan. This model gives a house completely friendly to nature and the environment and knowledge-oriented. The model contributes to housing programs addressing new requirements. Our proposed housing model and its general principles are replicable in other regions globally to use green energy sustainably.